Barriers to Implementation of Team Care and Interprofessional Education: the Viewpoints of Educational Managers of Iranian Health System - Zohreh Vafadar; Zohreh Vanaki; Abbas Ebadi (مجله ایرانی آموزش در علوم پزشکی, 2015)
Introduction: Today, interprofessional collaboration and team care as well as interprofessional education are inevitable necessities for addressing healthcare needs of societies. Due to a contradiction between the need to provide team care at health centers and the lack of prioritization and implementation of team-based and interprofessional approaches to education in the health system, this study was conducted to explain the barriers to implementation of team care and interprofessional education in Iran from the viewpoints of educational managers of the health system. Methods: This qualitative content analysis study with a conventional approach was carried out from August 2013 to Jul 2014. The data were collected through semi–structured individual interviews with 16 educational managers and researchers in universities of medical sciences and medical education development centers who were selected by purposive sampling. All interviews were transcribed word by word and then analyzed using MAXQD software. Results:Two categories and eight subcategories were identified explaining the barriers to implementation of team care and interprofessional education from educational managers’ viewpoints. The two main categories included cultural-attitudinal barriers and structural-functional barriers. The first category consisted of subcategories such as weakness of systemic thinking, individualistic culture, profession-orientedness, physicians’ predominance, and role models. The second category included subcategories of management structure, stunted growth of educational management, inadequate understanding and weak evidence. Conclusion:Existent barriers and their influence on each other have prevented the implementation of team care and interprofessional education by creating a vicious cycle. Since the cultural and attitudinal changes occur over a long period, it is necessary to move towards changing the culture and attitudes and implementing team care and interprofessional education through restructuring the educational management as well as implementation of interprofessional education pilot programs and developing research and evidence accordingly.